Analysis of the communication of adverse events from the perspective of the nurses directly involved in patient care - Ilse Maria Tigre de Arruda Leitão; Roberta Meneses Oliveira; Sarah de Sá Leite; Marina Castro Sobral; Sarah Vieira Figueiredo; Mariana Correia Cadete (Universidade Federal do Ceará, 2014)
This descriptive study aimed to analyze the process of communicating adverse events in the hospital context, from the nurses' perspective. Data was collected in January 2013 in a public hospital in Fortaleza, Ceará, Brazil. A semi-structured interview was held with 37 nurses, covering guiding questions regarding the communication/recording of adverse events. It was found that communication of adverse events exists in the service, but that cases are under-reported and inadequately analyzed; the nurses were not unanimous in identifying the documents indicated for recording events; and a punitive culture predominates in the situations which generate adverse events, evidenced by reports of practices of reprimanding and punishment of the professionals. It is concluded that encouraging appropriate communication of adverse events in the service is necessary, considering recording as indispensable in the organizational communication process, as this is the source of data for analyzing the occurrence of adverse events and ensures patient safety.